2009
DOI: 10.2319/080808-418r.1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Degree of Conversion of Orthodontic Adhesives

Abstract: Objectives:To test the hypothesis that there is no difference in the cytotoxicity related to the modes of polymerization of five commercially available orthodontic bonding resins, with and without an oxygen-inhibited layer (OIL), and to evaluate the degree of conversion (DC) of these resins and correlate this to cytotoxicity. Materials and Methods: Five commercially available orthodontic bonding resins were tested for cytotoxicity and DC. Thirty-six disks of standardized dimensions, for each resin, were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 14 publications
4
33
2
1
Order By: Relevance
“…We used micro-Raman in situ to determine the CD of dentin adhesives 40) . Our results are slightly greater than reported in other studies with FTIR spectroscopy [41][42][43] . Although a positive correlation has been reported between hardness and DC, high CD does not necessarily mean higher mechanical properties 39) .…”
Section: Discussioncontrasting
confidence: 57%
“…We used micro-Raman in situ to determine the CD of dentin adhesives 40) . Our results are slightly greater than reported in other studies with FTIR spectroscopy [41][42][43] . Although a positive correlation has been reported between hardness and DC, high CD does not necessarily mean higher mechanical properties 39) .…”
Section: Discussioncontrasting
confidence: 57%
“…In a study by Jagdish et al [23], the authors analyzed the correlation between the degree of conversion of orthodontic adhesives, structurally close to restorative materials, and their cytotoxic effects in vitro. The quoted authors reported no significant association between the conversion degree of the material and impact of its samples on the intensity of metabolism in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date many studies focused on their physical properties, such as shear bond strength (Finnema et al, 2010), with less emphasis on RBDM biocompatibility, despite the proximity of their application site to the periodontal tissues which may cause inflammation of gingiva, oral mucosa and alveolar bone (Borra et al, 2009). Different studies, dealing with RBDM biocompatibility, are based on in vitro tests because of the ability to control the environment and cellular responses (Jagdish et al, 2009;Franz et al, 2003;Malkoc et al, 2010). According to the strategies for material testing, presented by Wataha (2012), the purpose of our study, was to determine in vitro material liability, the dynamics of any component release and the potential of released monomers to alter cell metabolism and function.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete RBDM conversion and/or their degradation in the oral environment causes the release of monomers which may affect adjacent tissues (Jagdish et al, 2009;Gioka et al, 2005). Light-cured or chemically cured dental composite resins leave a soft, sticky superficial layer upon polymerization, commonly referred to as an Oxygen-Inhibited Layer (OIL) because of its origin (Suh, 2004).…”
Section: Introductionmentioning
confidence: 99%